A framework for neuromotor and neurofunctional rehabilitation using multi-agent systems - Valente, Felipe R; Guimarães, Marcelo De P; Cirilo, Elder J R; Brandão, Alexandre F; Dias, Diego R C (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
Degenerative diseases and stroke disable many people, so investigating methods for rehabilitating patients is necessary. Thus, using the framework for creating virtual environments to work with neuromotor and neurofunctional rehabilitation, benefits can be achieved using virtual environments and body tracking devices. Developing such applications involves many requirements, such as constructing virtual environments, data storage, interaction with input devices, processing, and communication in rehabilitation sessions. In this paper, the proposal and development of a multi-agent framework are presented to facilitate the development of software for neuromotor and neurofunctional rehabilitation, providing advantages for developers, such as eliminating the need for code rewriting, facilitating the reuse of coding standards, and decreasing the time to develop new features.